2004
DOI: 10.1140/epjc/s2004-01966-2
|View full text |Cite
|
Sign up to set email alerts
|

Signals of new physics in global event properties in pp collisions in the TeV energy domain: rapidity intervals

Abstract: The study of possible new physics signals in global event properties in pp collisions in the TeV energy domain is extended from full phasespace to rapidity intervals experimentally accessible at LHC. The elbow structure in the total multiplicity distribution predicted in full phasespace is clearly present also in restricted rapidity intervals, leading to very strong charged particle correlations. It is also found that energy densities comparable to those reached in heavy ion collisions at RHIC could be attaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A sign of the component is seen also in the minimum biased data measured by the LHCb Collaboration in the forward region. The analysis of the LHC data on MD excludes interpretation of this Poisson-like component in terms of hard processes which could lead to 'elbow-like' behavior at the tail of the distributions considered in [27].…”
Section: Discussionmentioning
confidence: 96%
“…A sign of the component is seen also in the minimum biased data measured by the LHCb Collaboration in the forward region. The analysis of the LHC data on MD excludes interpretation of this Poisson-like component in terms of hard processes which could lead to 'elbow-like' behavior at the tail of the distributions considered in [27].…”
Section: Discussionmentioning
confidence: 96%
“…The extrapolation of the weighted superposition of the two defined classes of events from the TeV to the multi-TeV energy domain and a study of the properties of particle clans raised intriguing questions concerning the onset of a third class of events in the tail of the distribution, both in the full phase space [6] and in the limited windows in pseudorapidity [7]. Later study [8] of the MDs measured at √ s = 7 TeV indicated the existence of the third multiplicity component at low n. In this region, near the maximum of P(n), there is a suitable tool, the method of combinants [9], to be used in searching for new phenomena in the behavior of the MDs.…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation is also supported by more sophisticated theoretical calculations, in a scenario in which a time-dependent pulse for the initial strength of the color field is considered [95,96]. The large enhancement of the baryon-to-meson ratios demonstrates that SCF could play an important role in multiparticle production in pp collisions at LHC energies and that high energy density fluctuations can reach very high densities, potentially comparable to those reached in central Au + Au collisions at RHIC energies [97].…”
Section: A Baryon-to-meson Ratiomentioning
confidence: 81%